Type and Impact of Conflict Issues in The Film “The Batman” 2022 - Poppy Dwi Nurasih (Journal of Religion and Film, 2023)
This research discusses the issue of conflict in the film The Batman 2022. This film tells about someone who calls himself The Riddler who has killed several Gotham city officials and uncovers the dark side of them all which causes conflicts with several parties. Conflict is disagreement between several parties due to differences of opinion. This study aimsto describe the types of conflicts described by criminals, as well as to find out what impacts occur. Therefore, the researcher used a sociological approach. Researchers also use two theories, namely the theory of Nina Genneby and Ruben Markosyan, and the theory of Kun Maryati and Juju Suryawati. In addition, researchers used descriptive qualitative research methods to analyze this film. The results of this study are two types of conflict, interpersonal conflict and inter-group conflict. The seven positive impacts are: increased internal solidarity, lead to an interestingrelationships between groups, arouse citizens who are passively, emergence of strong individuals, directing innovation, as a means of evaluation, and new compromises. Then there are four negative impacts, namely: breaking of relationships between individuals and group unity, damage to property and loss of human life, changes in individual personality, and the last is the domination of the winning group.